Optimal agglomerate configurations and strain dependence of activation energies on Cu(001) surfaces - Coronado Matutti, Alberto (2006)
One of the most important aspects in the epitaxial growth of thin films is the mobility of adatoms and small agglomerates. As this mobility is related to activation energies, many studies are focused on calculating and determining the role of these energies. For example, previous studies showed that activation energies can be easily modified using deformation fields. However, many aspects are still not very clear. In this work we employed Genetic Algorithms to calculate optimal configurations of aggregates on Cu(001) surfaces modeled with the embedded atom method (EAM). The optimal configurations obtained showed no dependence on the applied strain. Additionally, we studied the dependence of the hopping and exchange activation energies on the applied strain level. It was observed that the hopping shows a clear dependence with respect to the biaxial tension or compression, in contrast to the exchange, whose dependence is more complex.